The role of social economy projects in the socio-spatial restructuring of rural areas: A contrasting study of a European and a Latinamerican case - Mateus, C. (RN37 Young scholars' Pre-Conference day 2022, 2022)
In the last decades, the historical marginalization of rural territories (political, economic, cultural and epistemologically) have been contested by many groups and movements from civil society. Tendencies of counter-urbanization (Anthopoulou, Nikolaos, & Petrou, 2017) and of repeasantization (Van der Ploeg, 2008) have been questioning the established hegemonic urban way of life all around the world. On one side, even though these tendencies are showing up in many researches, most of them only focus on these movements at the local scale without analysing their relation with the macro (global) scale. On the other side, there is a gap in the understanding of these movements simultaneously in the Global North and in the global South. Aiming to answer these questions, we ask: How can social economy practices in rural territories set a new alternative model of development? Within this question, two goals are set: (1) to understand how these practices are conceived (agents, associated values, production and reproduction models and social practices); and (2) to understand which model of development these dynamics are proposing for the inhabitancy of rural territories (proposed ideology, effective results/consequences of spatial practices, relation with the hegemonic mode of development). Visioning this, a sample of four currently active initiatives will be taken in consideration. Two of these will be based in Portugal and two in Ecuador, in order to allow a contrasting relational comparison (Hart, 2002) between Global North and South. Two of them will be in an initial stage of development (less than 5 years) and two in a more advanced stage of development (more than 5 years) in order to better understand how these projects relate to the macro tendencies and pressures. The methodology used will be based in a multi-scale analysis (from micro to macro) and it will make use of anthropological methods of analysis (such as semi-structured interviews and participant observation) combined with bibliographical review and mappings. This research aims to inform new politics and social tendencies that can change or are already changing the “urban” life in rural contexts, visioning to contribute to the collaborative design and production of these areas.